ANALISIS PERUBAHAN GARIS PANTAI AKIBAT TANAH LONGSOR DAN ABRASI (STUDI KASUS: DESA SIMPANG AYAM, BENGKALIS) - Randhi Saily; Sjelly Haniza; Mulyadi; Vinka Lyona; Intan Monica MG; Endah Kurniyaningrum (Racic : Rab Construction Research, 2025)
Simpang Ayam Village is located in Bengkalis District, Bengkalis Regency, Riau Province. This coastal area consists of peatland and faces the Malacca Strait, making it vulnerable to wave-induced abrasion. At the end of 2022, a significant landslide occurred in Simpang Ayam Village, causing substantial shoreline changes and resulting in the loss of dozens of hectares of land to the sea. Conducting manual investigations in the landslide-affected area is not feasible due to continuous land movement towards the sea, posing serious safety risks. Remote sensing technology offers an effective method to analyze shoreline changes using the Modified Normalized Difference Water Index (MNDWI) and vegetation density changes through the Normalized Difference Vegetation Index (NDVI). This study utilizes Sentinel-2 medium-resolution satellite imagery to assess these changes. The results indicate a noticeable shift in the shoreline, marked by landward advancement, and a decline in vegetation density, as evidenced by a vegetation index decrease of more than -0.1. Furthermore, the total landslide-affected area was 36.89 hectares, with the largest landslide occurring at Location 3 (15.96 hectares) and the smallest at Location 9 (0.49 hectares).